The golden (hands) rule: Exploring user experiences with gamepad and natural-user interfaces in popular video games. Issue 1 (1st March 2017) - Bowman, Nicholas David; Pietschmann, Daniel; Liebold, Benny
This research report sought to understand how gamers experienced recent gaming sessions using traditional game controllers (gamepads) or natural user interfaces (NUIs, such as the Nintendo Wiimote). A secondary qualitative analysis of N=238 open-ended comments to a larger game controller experience survey were analysed for emergent themes, with χ2 tests used to compare the frequency of their mention between the two controller types. While the same eleven discussion themes emerged when players described either gamepad or NUI experiences, participants discussing gamepads were more likely to comment on the controller's precision, comfort, success using the controller, and their past experience with the controller. Likewise, participants discussing NUIs were more likely to comment on the controller's lack of precision, feeling unnatural, having less success during the game session, and seeing the controller as more novel. No differences in controller simplicity or the overall enjoyment were found. Additionally, game genre differences were found suggesting shooting games (first- and third-person shooters) to be more frequently played with gamepads and sports games to be more frequently played with NUIs, and gamepad session were as much as 50 per cent longer on average. This research supports and extends prior findings which suggest that NUIs might not be as natural and intuitive as they are designed to be.